Spastic cerebral palsy and quality of life in children aged 6-12 years: exploring key associated factors - Koru, Lütfiye; Güler, Serhat; Saltık, Sema (The Turkish Journal of Pediatrics, 2025)
Background. Children with cerebral palsy (CP) may experience epilepsy and challenges with movement, posture, cognition, and musculoskeletal development, which can impact their quality of life (QOL). In this study, we investigated the relationship between demographic and clinical variables as well as QOL in children with spastic CP.Methods. Children aged 6 to 12 years with CP who were followed-up at our tertiary center were included in this cross-sectional study, regardless of the cause. They were categorized into groups based on their gestational age, motor function levels, accompanying conditions such as epilepsy and intellectual disability, and demographic variables, including mothers’ education and income levels. Subsequently, the QOL scores of these groups were compared. Among the 9-12 age group, those with sufficient intellectual capacity completed the QOL questionnaire by both the mothers and patients themselves. The Children’s Sleep Habits Questionnaire (CSHQ) was evaluated and compared with the QOL scores of the patients.Results. A total of 71 patients were included in the study (42 males, 59%). Children whose mothers were more educated and had higher in income level, who were ambulatory with hemiplegia, and did not have epilepsy had significantly better QOL scores. Those with better CSHQ scores were found to have significantly better QOL scores. Additionally, the responses of mothers and patients within the 9-12 age group were highly compatible.Conclusion. Children with CP face challenges impacting their daily lives and overall QOL. Our study identified factors linked to the QOL of children with spastic CP and showed that their integration into CP management could enhance their well-being.
Keywords: cerebral palsy; epilepsy; quality of life; sleep disorder